PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAKAN PENGANIAYAAN DI INDONESIA - MARIA CRISTY, ELSA; Zukriadi, Diki (LPPM Universitas Putera Batam, 2024)
This research explores the legal protection for victims of acts of violence in Indonesia, with a focus on the role of existing legal policies and regulations. Although a legal framework has been established to address violence and protect victims, significant challenges continue to hinder the effectiveness of the victim protection system in the context of violence. This study employs qualitative methods, including interviews and document analysis, to delve into the issues faced by victims and evaluate the applicable policies and regulations. The research results identify the need for increased public awareness of victims' rights, improved law enforcement, and enhanced accessibility to legal assistance and support services. With these measures, it is expected that the victim protection system for acts of violence in Indonesia can be improved, ensuring better protection of victims' rights and interests. Keywords: Legal protection, victims of acts of violence, legal policies, legal regulations, Indonesia..